Reliability emulation of production system on longwall face - Hao, Bing-yuan; Sui, Gang; Kang, Li-xun (Journal of coal science & engineering, China, 2009)
Based on the theory of random process and the characteristic of the functioning of a system component subject to a certain specific probability distribution, emulated the whole process of system production on Iongwall face was emulated, in which the methods of time pace and computer random emulation were adopted. The paper provides an objective basis for the analysis of a mining Iongwall face and the varied lines of effectiveness, machine stoppage rate and coal flow of components and system, and output etc.lt also offers some theories to improve productivity by discussing the application of the transformation plan and optimization of reasonable coal stock capacity, as well as selection of system equipment and matching optimization.